DETECTION IS BACTERIA IN DRINKING WATER IN THE PACKAGING GALLON - Asih Rahayu (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2010)
Twenty four of thirty drinking water samples taken from each gallons has been identified as containing some bacteria with TPC indicator number 1 to 22 CFU/ml. TPC number of whole samples shows that the bacteria number tend to increase after it stored in water dispenser for some period of time. In two days, the TPC number has reached 2 to 98 CFU/ml, and after four days it reached 3 to 166 CFU/ml. Research shows that he three samples are not consumable after it stored in water dispenser for four days, since it contains bacteria with TPC number more than 100 CFU/ml. The increase of bacteria numbers, as the water stored in dispenser, might be caused by the reproduction of bacteria which has initially contaminated the drinking water. Otherwise, the increase of TPC number might also be caused by the bacteria in water dispenser itself. It is recommended for the consumer to clean the water dispenser before they exchange the gallons to prevent bacteria contamination in their drinking water.